The Kind of Brave You Wanted to Be : Prose Prayers and Cheerful Chants against the Dark - Doyle, Brian, 1956 November 6-2017 May 27 (Book collections on Project MUSE., 2016)
"Proems, taut tales, small stories with rhythm and blues and grace and bruise and laughter between the lines. Brian Doyle's The Kind of Brave You Wanted to Be is a book of cadenced notes on the swirl of miracle and the holy of attentiveness; a book about children and birds, love and grief and everything alive, which is to say all prayers. Brian Doyle's uncategorizable form is the brief story dressed like a poem but with the loose lyricism and verve of an essay. Here are chants and litanies, like gentle songs to the sacrament of every moment"--